MDMA 'ecstasy' increases cerebral cortical perfusion determined by bolus‐tracking arterial spin labelling (btASL) MRI. (12th June 2013) - Rouine, J; Gobbo, O L; Campbell, M; Gigliucci, V; Ogden, I; McHugh Smith, K; Duffy, P; Behan, B; Byrne, D; Kelly, M E; Blau, C W; Kerskens, C M; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose The purpose of this study was to assess cerebral perfusion changes following systemic administration of the recreational drug 3, 4‐methylendioxymethamphetamine (MDMA 'ecstasy') to rats. Experimental Approach Cerebral perfusion was quantified using bolus‐tracking arterial spin labelling (btASL) MRI. Rats received MDMA (20 mg·kg−1; i.p.) and were assessed 1, 3 or 24 h later. Rats received MDMA (5 or 20 mg·kg−1; i.p.) and were assessed 3 h later. In addition, rats received MDMA (5 or 10 mg·kg−1; i.p.) or saline four times daily over 2 consecutive days and were assessed 8 weeks later. Perfusion‐weighted images were generated in a 7 tesla (7T) MRI scanner and experimental data was fitted to a quantitative model of cerebral perfusion to generate mean transit time (MTT), capillary transit time (CTT) and signal amplitude. Key Results MDMA reduces MTT and CTT and increases amplitude in somatosensory and motor cortex 1 and 3 h following administration, indicative of an increase in perfusion. Prior exposure to MDMA provoked a long‐term reduction in cortical 5‐HT concentration, but did not produce a sustained effect on cerebral cortical perfusion. The response to acute MDMA challenge (20 mg·kg−1; i.p.) was attenuated in these animals indicating adaptation in response to prior MDMA exposure. Conclusions and Implications MDMA provokes changes in cortical perfusion, which are quantifiable by btASL MRI, a neuroimaging tool with translational potential. Future studies are directed towards elucidation of the mechanisms involved and correlating changes in cerebrovascular function with potential behavioural deficits associated with drug use.